The Existence Of Adat Law Related To Land Right Transaction After Unification Of Indonesian Agrarian Law: The Problem Of Legal Transplant - Joesoef, Iwan Erar (Veteran Law Review, 2018)
Legal transaction related to land still facing some problem in its implementation after government of Indonesia appointed Law No. 5 Year 1960 concerning Basic Regulations on Agrarian Principles. The main problem is, in one side, such Law No. 5 Year of 1960 is based on the Adat Law concept as the Indonesian Living Law, and the other side is, in modern practicing of transaction of which using Western Law concept as global main stream which are transplanted into the National Positive Regulation including National Positive Land Law. The legal questions are how about the existence and its implementation of Adat Law concept especially the conception of land right transfer (“Terang, Riil dan Tunai”) concept and how should the government to take legal transplant of such concepts simultaneously (Adat Law and Western Law) which giving the legal certainty for both parties under National Positive Land Law. This conceptual article will elaborate how to make a good academic of legal transplant as Otto Kahn-Freund says that the laws should suit with the society of which the laws is made.